The credible identification at the level of speculation from a stock market ethics perspective - De La Vega Meneses, Jose Gerardo (2023)
The development of quantitative tools to guide decision-making in the capital markets are elements that can be innovated for the benefit of optimizing the investment, depending on the risk profile of the investor. In this context, the research problem was to propose a methodology to identify the degree or speculative level in investments in the Mexican capital market, represented by the Price and Quotation Index of the Mexican Stock Exchange during the period 2015 to 2021. The methodology used in this research was quantitative, documentary and descriptive, analyzing the historical performance during the period 2015 to 2021 of strategic multiples of market value in the companies listed in the Price Index of the Mexican Stock Exchange. The period 2015 to 2021 was analyzed, obtaining the information from the Reuters Eikon platform, quantitatively and graphically analyzing the behavior of the multiples of market value to book value, market value to income, and market value to cash flow, with the in order to propose an innovative methodology to identify the speculative degree in the share price of the companies analyzed, in order to encourage the development of this methodology in other capital markets.